Highly flame-retardant and anti-corrosion fiberglass asphalt shingle and preparation method thereof
By using nylon, melamine polyphosphate and glass fiber in building roof tiles, and double curing with asphalt-covered fiber membrane, sprayed graphene and coated flame retardant, the structural problems and fire safety hazards of the tiles at high and low temperatures are solved, and efficient waterproof, anti-corrosion and flame retardant effects are achieved.
Patent Information
- Application Number
- CN202311804804.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-12-26
AI Technical Summary
The roof tiles of existing buildings soften at high temperatures and break at low temperatures, making them prone to water leakage and sand loss, and are prone to mold and breed bacteria, and release toxic gases during combustion, posing fire and safety hazards.
Long fibers are prepared by microwave-assisted melting and pultrusion by microwave-assisted melting of nylon, melamine polyphosphate and glass fiber, combined with asphalt, coated fiber membranes, sprayed graphene and coated flame retardant, and double curing is carried out to produce high flame retardant and anti-corrosion glass fiber asphalt shingles.
The waterproof, corrosion and flame retardant properties of the tiles are achieved, which enhances the structural stability and safety of the tiles and avoids the risks of fire and toxic gas release.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a highly flame-retardant and anti-corrosion glass fiber asphalt shingle and a preparation method thereof. Background Art
[0002] Most building roofs are still sloping roofs, and tiles are still the main wind and rain protection for sloping roofs. However, the colored sand layer of ordinary tiles is made of sintered sand, which is easy to fall off after about 3 years of use. The asphalt layer is greatly affected by temperature. It is easy to soften and deform at high temperatures, and easy to crack, leak, and lose sand at low temperatures. When it rains, rainwater will penetrate into the colored sand layer and reach the surface of the asphalt layer. If it is left still for a long time, it will mold and breed bacteria. In addition, the housing density is getting higher, especially in winter, the air is dry, and fires are prone to occur. In addition, a large amount of toxic gases and smoke will be released during the combustion process. For people, if they are accidentally inhaled, it may be life-threatening. Therefore, it is particularly important to invent a highly flame-retardant and anti-corrosion fiberglass asphalt tile. Summary of the invention
[0003] The object of the present invention is to provide a highly flame-retardant and anti-corrosion glass fiber asphalt shingle and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a highly flame retardant and anti-corrosion glass fiber asphalt shingle, which is made by mixing long fibers with asphalt, then coating with fiber membrane, spraying with graphene and coating with flame retardant, and then double curing.
[0005] Furthermore, the long fibers are prepared from nylon 66, melamine polyphosphate and glass fiber by microwave-assisted melt pultrusion.
[0006] Furthermore, the fiber membrane is prepared by using 3-methoxy-2-methylchloromethylacrylonitrile through magnetic field-electrospinning.
[0007] Furthermore, the flame retardant is prepared from 3-isocyanatepropyltriethoxysilane-modified pentaerythritol phosphate composite butyl acrylate.
[0008] Furthermore, the dual curing is respectively cured by moisture and ultraviolet light.
[0009] Furthermore, a method for preparing highly flame-retardant and anti-corrosion glass fiber asphalt shingles comprises the following preparation steps:
[0010] (1) After drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (4 to 6 times the mass of nylon 66), glass fiber (2 to 3 times the mass of nylon 66), polyphosphate melamine (0.1 to 0.3 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.7 to 0.9 times the mass of nylon 66), stir at 350 to 500 rpm for 30 to 90 minutes, perform microwave-assisted melt pultrusion to obtain long fibers, dry at 65 to 75°C for 10 to 14 hours, add No. 90 matrix asphalt (270 to 350 times the mass of nylon 66), heat to 105 to 130°C, stir evenly, pour into a mold, and cure at 50 to 70°C for 22 to 26 hours to obtain glass fiber asphalt shingles;
[0011] (2) 3-methoxy-2-methylchloromethacrylonitrile, N,N-dimethylacetamide, and silicon dioxide are mixed in a mass ratio of 4:20:0.5 to 8:23:1, stirred at 300 to 400 rpm for 3 to 6 hours, and ultrasonicated at 21 kHz for 2 hours to obtain a spinning solution, and subjected to magnetic field-electrostatic spinning on glass fiber asphalt shingles in an environment of temperature of 25° C. and humidity of 30%, dried at 65 to 75° C. for 10 to 14 hours, and then graphene is sprayed with laser-assisted low pressure;
[0012] (3) Pentaerythritol phosphate and dioxane are mixed in a mass ratio of 20:45 to 30:60, stirred at 300 to 400 rpm for 90 to 150 min, heated to 70 to 90° C., 0.15 to 0.25 times the mass of pentaerythritol phosphate of 3-isocyanatopropyltriethoxysilane is added dropwise at 0.7 g / s, reacted for 30 to 60 min, 0.9 to 1.2 times the mass of pentaerythritol phosphate of melamine polyphosphate is added, acetic acid is added until the pH value of the solution is 3 to 5, the reaction is continued for 2 to 4 h, cooled to room temperature, filtered, the solid is taken, washed with anhydrous ethanol 3 to 5 times, and dried at 65 to 75° C. for 4 to 5 h to obtain intermediate A;
[0013] (4) Mix the intermediate A, butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylacetone in a mass ratio of 25:35:2:1.5:5:15:0.2 to 35:45:3:2:8:24:0.5, and stir at 1450 to 1600 rpm for 30 to 60 minutes to obtain a flame retardant;
[0014] (5) The flame retardant is coated on the glass fiber asphalt shingles sprayed with graphene to a thickness of 0.3 to 0.8 mm, and double curing is performed to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles.
[0015] Furthermore, the process parameters of the microwave-assisted melt pultrusion in step (1) are: microwave power 260 W, melting tank temperature 250° C., traction speed 20 m / min, and screw speed 100 r / min.
[0016] Furthermore, the process parameters of the magnetic field-electrospinning in step (2) are: magnetic field intensity 0.3T, magnet spacing 2.5cm, spinning flow rate 10mm / min, positive voltage 25kV, negative voltage 2kV, and receiving distance 15cm.
[0017] Furthermore, the process parameters of the laser-assisted low-pressure spraying in step (2) are: spray gun preheating temperature 200-600°C, nitrogen pressure 0.8MPa, spraying distance 15cm, scanning speed 30mm / s, powder feeding rate 25g / min, and laser irradiation power 600W.
[0018] Furthermore, the conditions of the double curing in step (5) are as follows: the first moisture curing is performed at a temperature of 25 to 27° C., a humidity of 75 to 80%, and a time of 22 to 26 hours; the second UV curing is performed at a light source of UV light, a main wavelength of 365 nm, a power of 1 kW, an irradiation distance of 15 cm, and a time of 20 minutes.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention utilizes nylon, melamine polyphosphate and glass fiber to prepare long fibers through microwave-assisted melt pultrusion, wherein nylon and melamine polyphosphate have strong absorption performance for microwaves, thereby increasing the viscosity of the matrix, and even under the action of water damage, its structure is difficult to be destroyed, and the amide group of nylon and the phosphate group can be polarly combined to enhance the interfacial force, and the non-polar long chain in melamine polyphosphate can block the penetration of water molecules, so that the matrix can achieve waterproof and anti-corrosion effects; then the long fibers are mixed with asphalt, and then coated with fiber membranes, sprayed with graphene and coated with flame retardants to obtain asphalt tiles, so as to achieve waterproof, flame retardant and anti-corrosion effects.
[0021] Firstly, the present invention utilizes 3-methoxy-2-methylchloromethyl methacrylonitrile to prepare fibers through magnetic field-electrospinning. Since the jet is subjected to Lorentz magnetic force, an orderly and uniform spinning film is obtained, which is coated on the surface of the asphalt shingle. Then, laser-assisted low-pressure spraying of graphene is used. Under the synergistic effect of high-speed impact and synchronous laser heating and softening, the asphalt and the fiber film are tightly combined. In addition, the graphene can well fill the gaps in the matrix, so that the two-dimensional sheet structure forms a dense physical insulation layer, thereby improving the waterproof, anti-corrosion and flame-retardant properties of the matrix.
[0022] Secondly, pentaerythritol phosphate is modified with 3-isocyanatopropyltriethoxysilane. Under high temperature conditions, dehydration condensation occurs to form polysiloxane, and pentaerythritol phosphate is grafted into polysiloxane through hydroxyl groups to promote the fusion of polysiloxane and butyl acrylate. In the combustion process, it can delay the decomposition of pentaerythritol phosphate in the early stage, and promote the dehydration and cross-linking of a large number of phosphorus-containing free radicals and pentaerythritol in the later stage to form a continuous and tight carbon layer, which effectively protects the substrate and improves the flame retardant performance; then it is cured on the asphalt shingles through moisture / light dual curing, in which the isocyanate group can react with moisture in the air to form urea bonds, causing the molecules to cross-link, and then irradiated with ultraviolet light to strengthen the curing, forming a film with excellent performance on the surface of the substrate, thereby enhancing the waterproof, anti-corrosion and flame retardant properties of the tiles. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the highly flame retardant and anti-corrosion glass fiber asphalt shingles prepared in the following examples are as follows:
[0025] Waterproofing: The same size of the embodiment and the comparative example were soaked in distilled water. After 7 days, the surface moisture was wiped off with filter paper. The weight change of the sample before and after soaking was weighed, and its water absorption rate was detected; water absorption rate = (weight after soaking - weight before soaking) / weight before soaking × 100%.
[0026] Anticorrosion: The same size of the embodiment and the comparative example were subjected to acid and alkali resistance tests. The samples were immersed in 30wt% sulfuric acid solution and 10wt% sodium hydroxide solution for 7 days, respectively, and their changes were observed.
[0027] Flame retardant: The same size of the embodiment and the comparative example were subjected to the UL94 vertical combustion test and their LOI was detected
[0028] Example 1
[0029] (1) After drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (4 times the mass of nylon 66), glass fiber (2 times the mass of nylon 66), polyphosphate melamine (0.1 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.7 times the mass of nylon 66), stir at 350rpm for 30 minutes, and perform microwave-assisted melt pultrusion. The process parameters are: microwave power 260W, melting tank temperature 250°C, traction speed 20m / min, screw speed 100r / min, and obtain long fibers. Dry at 65°C for 10 hours, add No. 90 matrix asphalt (270 times the mass of nylon 66), heat to 105°C, stir evenly, pour into a mold, and cure at 50°C for 22 hours to obtain glass fiber asphalt shingles;
[0030] (2) 3-methoxy-2-methylchloromethylacrylonitrile, N,N-dimethylacetamide, and silicon dioxide were mixed in a mass ratio of 4:20:0.5, stirred at 300 rpm for 3 h, and ultrasonicated at 21 kHz for 2 h to obtain a spinning solution. The spinning solution was subjected to magnetic field-electrostatic spinning on glass fiber asphalt shingles in an environment of temperature of 25°C and humidity of 30%. The spinning process parameters were: magnetic field intensity of 0.3 T, magnet spacing of 2.5 cm, spinning flow rate of 10 mm / min, positive voltage of 25 kV, negative voltage of 2 kV, receiving distance of 15 cm, and dried at 65°C for 10 h. Graphene was then sprayed at low pressure with the assistance of laser. The spraying process parameters were: spray gun preheating temperature of 200°C, nitrogen pressure of 0.8 MPa, spraying distance of 15 cm, scanning speed of 30 mm / s, powder feeding rate of 25 g / min, and laser irradiation power of 600 W.
[0031] (3) Pentaerythritol phosphate and dioxane were mixed at a mass ratio of 20:45, stirred at 300 rpm for 90 min, heated to 70° C., 0.15 times the mass of pentaerythritol phosphate of 3-isocyanatopropyltriethoxysilane was added dropwise at 0.7 g / s, reacted for 30 min, 0.9 times the mass of pentaerythritol phosphate of melamine polyphosphate was added, acetic acid was added until the pH value of the solution was 3, the reaction was continued for 2 h, cooled to room temperature, filtered, the solid was taken, washed with anhydrous ethanol 3 times, and dried at 65° C. for 4 h to obtain intermediate A;
[0032] (4) Mixing intermediate A, butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylacetone in a mass ratio of 25:35:2:1.5:5:15:0.2, and stirring at 1450 rpm for 30 min to obtain a flame retardant;
[0033] (5) The flame retardant is coated on the glass fiber asphalt shingles sprayed with graphene with a thickness of 0.3 mm, and double curing is performed. The first moisture curing: the temperature is 25°C, the humidity is 75%, and the time is 22 hours; the second UV curing: the light source is UV light, the main wavelength is 365nm, the power is 1kW, the irradiation distance is 15cm, and the time is 20min, to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles.
[0034] Example 2
[0035] (1) After drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (5 times the mass of nylon 66), glass fiber (2.5 times the mass of nylon 66), polyphosphate melamine (0.2 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.8 times the mass of nylon 66), stir at 425rpm for 65min, and perform microwave-assisted melt pultrusion. The process parameters are: microwave power 260W, melting tank temperature 250°C, traction speed 20m / min, screw speed 100r / min, and obtain long fibers. Dry at 70°C for 12h, add No. 90 matrix asphalt (310 times the mass of nylon 66), heat to 120°C, stir evenly, pour into a mold, and cure at 60°C for 24h to obtain glass fiber asphalt shingles;
[0036] (2) 3-methoxy-2-methylchloromethylacrylonitrile, N,N-dimethylacetamide, and silicon dioxide were mixed in a mass ratio of 6:21.5:0.75, stirred at 350 rpm for 4.5 h, and subjected to ultrasound at 21 kHz for 2 h to obtain a spinning solution. The spinning solution was subjected to magnetic field-electrospinning on glass fiber asphalt shingles in an environment of 25°C and 30% humidity. The spinning process parameters were: magnetic field intensity 0.3 T, magnet spacing 2.5 cm, spinning flow rate 10 mm / min, positive voltage 25 kV, negative voltage 2 kV, receiving distance 15 cm, and dried at 70°C for 12 h. Graphene was then sprayed at low pressure with the assistance of laser. The spraying process parameters were: spray gun preheating temperature 400°C, nitrogen pressure 0.8 MPa, spraying distance 15 cm, scanning speed 30 mm / s, powder feeding rate 25 g / min, and laser irradiation power 600 W.
[0037] (3) Pentaerythritol phosphate and dioxane were mixed in a mass ratio of 25:52.5, stirred at 350 rpm for 120 min, heated to 80° C., 0.21 times the mass of pentaerythritol phosphate of 3-isocyanatopropyltriethoxysilane was added dropwise at 0.7 g / s, reacted for 45 min, 1.1 times the mass of pentaerythritol phosphate of melamine polyphosphate was added, acetic acid was added until the pH value of the solution was 4, the reaction was continued for 3 h, cooled to room temperature, filtered, the solid was taken, washed with anhydrous ethanol three times, and dried at 70° C. for 4.5 h to obtain intermediate A;
[0038] (4) Mixing intermediate A, butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylacetone in a mass ratio of 30:40:2.5:1.75:6.5:19.5:0.35, and stirring at 1520 rpm for 45 min to obtain a flame retardant;
[0039] (5) The flame retardant is coated on the glass fiber asphalt shingles sprayed with graphene with a thickness of 0.6 mm, and double curing is performed. The first moisture curing: the temperature is 26°C, the humidity is 77%, and the time is 24 hours; the second UV curing: the light source is UV light, the main wavelength is 365nm, the power is 1kW, the irradiation distance is 15cm, and the time is 20min, to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles.
[0040] Example 3
[0041] (1) After drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (6 times the mass of nylon 66), glass fiber (3 times the mass of nylon 66), polyphosphate melamine (0.3 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.9 times the mass of nylon 66), stir at 500 rpm for 90 minutes, and perform microwave-assisted melt pultrusion. The process parameters are: microwave power 260 W, melting tank temperature 250°C, traction speed 20 m / min, screw speed 100 r / min, and obtain long fibers. Dry at 75°C for 14 hours, add No. 90 matrix asphalt (350 times the mass of nylon 66), heat to 130°C, stir evenly, pour into a mold, and cure at 70°C for 26 hours to obtain glass fiber asphalt shingles;
[0042] (2) 3-methoxy-2-methylchloromethylacrylonitrile, N,N-dimethylacetamide, and silicon dioxide were mixed in a mass ratio of 8:23:1, stirred at 400 rpm for 6 h, and ultrasonicated at 21 kHz for 2 h to obtain a spinning solution. The spinning solution was subjected to magnetic field-electrostatic spinning on glass fiber asphalt shingles in an environment of temperature of 25°C and humidity of 30%. The spinning process parameters were: magnetic field intensity of 0.3 T, magnet spacing of 2.5 cm, spinning flow rate of 10 mm / min, positive voltage of 25 kV, negative voltage of 2 kV, receiving distance of 15 cm, and dried at 75°C for 14 h to obtain the spun fibers, which were then sprayed with graphene using laser-assisted low-pressure spraying. The spraying process parameters were: spray gun preheating temperature of 600°C, nitrogen pressure of 0.8 MPa, spraying distance of 15 cm, scanning speed of 30 mm / s, powder feeding rate of 25 g / min, and laser irradiation power of 600 W.
[0043] (3) Pentaerythritol phosphate and dioxane were mixed at a mass ratio of 30:60, stirred at 400 rpm for 150 min, heated to 90° C., 0.25 times the mass of pentaerythritol phosphate of 3-isocyanatopropyltriethoxysilane was added dropwise at 0.7 g / s, reacted for 60 min, 1.2 times the mass of pentaerythritol phosphate of melamine polyphosphate was added, acetic acid was added until the pH value of the solution was 5, the reaction was continued for 4 h, cooled to room temperature, filtered, the solid was taken, washed with anhydrous ethanol 5 times, and dried at 75° C. for 5 h to obtain intermediate A;
[0044] (4) Mixing intermediate A, butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylacetone in a mass ratio of 35:45:3:2:8:24:0.5, and stirring at 1600 rpm for 60 min to obtain a flame retardant;
[0045] (5) The flame retardant is coated on the glass fiber asphalt shingles sprayed with graphene with a thickness of 0.8 mm, and double curing is performed. The first moisture curing: the temperature is 27°C, the humidity is 80%, and the time is 26 hours; the second UV curing: the light source is UV light, the main wavelength is 365nm, the power is 1kW, the irradiation distance is 15cm, and the time is 20min, to obtain highly flame-retardant and anti-corrosion glass fiber asphalt shingles.
[0046] Comparative Example 1
[0047] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: after drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (5 times the mass of nylon 66), glass fiber (2.5 times the mass of nylon 66), polyphosphate melamine (0.2 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.8 times the mass of nylon 66), stir at 425rpm for 65min, and perform melt pultrusion. The process parameters are: melting tank temperature 250°C, traction speed 20m / min, screw speed 100r / min, to obtain long fibers, dry at 70°C for 12h, add No. 90 base asphalt (310 times the mass of nylon 66), heat to 120°C, stir evenly, pour into a mold, and cure at 60°C for 24h to obtain glass fiber asphalt shingles; the remaining steps are the same as Example 2.
[0048] Comparative Example 2
[0049] The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: glass fiber and No. 90 matrix asphalt are mixed in a mass ratio of 1.5:110, heated to 120°C, stirred evenly, poured into a mold, and cured at 60°C for 24 hours to obtain glass fiber asphalt shingles; the remaining steps are the same as Example 2.
[0050] Comparative Example 3
[0051] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: 3-methoxy-2-methylchloromethyl acrylonitrile, N,N-dimethylacetamide, and silicon dioxide are mixed in a mass ratio of 6:21.5:0.75, stirred at 350rpm for 4.5h, and ultrasonicated at 21kHz for 2h to obtain a spinning solution. In an environment of temperature of 25°C and humidity of 30%, electrostatic spinning is carried out on the glass fiber asphalt shingle. The spinning process parameters are: spinning flow rate of 10mm / min, positive voltage of 25kV, negative voltage of 2kV, receiving distance of 15cm, drying at 70°C for 12h, and then laser-assisted low-pressure spraying of graphene is used. The spraying process parameters are: spray gun preheating temperature of 400°C, nitrogen pressure of 0.8MPa, spraying distance of 15cm, scanning speed of 30mm / s, powder feeding rate of 25g / min, and laser irradiation power of 600W; the remaining steps are the same as those in Example 2.
[0052] Comparative Example 4
[0053] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: laser-assisted low-pressure spraying of graphene onto glass fiber asphalt shingles, and the spraying process parameters are: spray gun preheating temperature 400°C, nitrogen pressure 0.8MPa, spraying distance 15cm, scanning speed 30mm / s, powder feeding rate 25g / min, laser irradiation power 600W; the remaining steps are the same as Example 2.
[0054] Comparative Example 5
[0055] The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: (2) 3-methoxy-2-methylchloromethyl acrylonitrile, N,N-dimethylacetamide, and silicon dioxide are mixed in a mass ratio of 6:21.5:0.75, stirred at 350rpm for 4.5h, and ultrasonicated at 21kHz for 2h to obtain a spinning solution. In an environment of temperature of 25°C and humidity of 30%, a magnetic field-electrostatic spinning is performed on the glass fiber asphalt shingle. The spinning process parameters are: magnetic field intensity of 0.3T, magnet spacing of 2.5cm, spinning flow rate of 10mm / min, positive voltage of 25kV, negative voltage of 2kV, receiving distance of 15cm, drying at 70°C for 12h, and then spraying graphene; the remaining steps are the same as Example 2.
[0056] Comparative Example 6
[0057] The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: (2) 3-methoxy-2-methylchloromethyl acrylonitrile, N,N-dimethylacetamide and silicon dioxide are mixed in a mass ratio of 6:21.5:0.75, stirred at 350rpm for 4.5h, and ultrasonicated at 21kHz for 2h to obtain a spinning solution. In an environment of temperature of 25°C and humidity of 30%, a magnetic field-electrostatic spinning is carried out on a glass fiber asphalt shingle. The spinning process parameters are: magnetic field intensity of 0.3T, magnet spacing of 2.5cm, spinning flow rate of 10mm / min, positive voltage of 25kV, negative voltage of 2kV, receiving distance of 15cm, drying at 70°C for 12h, and coating on a glass fiber asphalt shingle; the remaining steps are the same as those in Example 2.
[0058] Comparative Example 7
[0059] The difference between Comparative Example 7 and Example 2 is that step (3) is omitted, and step (4) is changed to: butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylpropanone are mixed in a mass ratio of 40:2.5:1.75:6.5:19.5:0.35, and stirred at 1520 rpm for 45 min to obtain a coating; the remaining steps are the same as those in Example 2.
[0060] Comparative Example 8
[0061] The difference between Comparative Example 8 and Example 2 is that step (5) is different. Step (5) is changed to: coating the flame retardant on the glass fiber asphalt shingles sprayed with graphene with a thickness of 0.6 mm, and performing UV light curing with a main wavelength of 365 nm, a power of 1 kW, an irradiation distance of 15 cm, and a time of 20 min to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles; the remaining steps are the same as Example 2.
[0062] Comparative Example 9
[0063] The difference between Comparative Example 9 and Example 2 is that step (5) is different. Step (5) is changed to: coating the flame retardant on the glass fiber asphalt shingles sprayed with graphene with a thickness of 0.6 mm, and moisture curing at a temperature of 26°C, a humidity of 77%, and a time of 24 hours to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles; the remaining steps are the same as Example 2.
[0064] Effect example
[0065] Table 1 below shows the performance analysis results of the highly flame retardant and anti-corrosion glass fiber asphalt shingles of Examples 1 to 3 of the present invention and Comparative Examples 1 to 9.
[0066] Table 1
[0067]
[0068] From the comparison of the test data of the embodiment and the comparative example in Table 1, it can be found that the long fibers prepared by microwave-assisted melt pultrusion of nylon, melamine polyphosphate and glass fiber in the present invention can be mixed with asphalt to increase the viscosity of the matrix. Even under the action of water damage, its structure is difficult to be destroyed, and the penetration of water molecules is blocked, so that the matrix can achieve waterproof and anti-corrosion effects. Then, 3-methoxy-2-methylchloromethyl methacrylonitrile is used to prepare an orderly and uniform spinning film through magnetic field-electrospinning, which is coated on the surface of the asphalt shingle, and then laser-assisted low-pressure spraying of graphene is used. The asphalt and the fiber membrane are tightly combined, and the graphene can fill the gaps in the matrix very well, so that the waterproof, anti-corrosion and flame retardant properties of the matrix are improved. Then, 3-isocyanatepropyltriethoxysilane is used to modify pentaerythritol phosphate and butyl acrylate to prepare a flame retardant, which can form a continuous and tight carbon layer during the combustion process, effectively protect the substrate, and improve the flame retardant properties of the matrix. Through moisture / light dual curing, the molecules are cross-linked to form a film with excellent performance on the surface of the matrix, thereby enhancing the waterproof, anti-corrosion and flame retardant properties of the tile.
[0069] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A highly flame retardant and anti-corrosion glass fiber asphalt shingle, characterized in that: The highly flame-retardant and anti-corrosion glass fiber asphalt shingles are made by mixing long fibers with asphalt, then coating with a fiber membrane, spraying with graphene, and applying a flame retardant, and then double curing.
2. The highly flame retardant and anti-corrosion fiberglass asphalt shingle according to claim 1, characterized in that: The long fiber is prepared from nylon 66, melamine polyphosphate and glass fiber by microwave-assisted melt pultrusion.
3. The highly flame retardant and anti-corrosion fiberglass asphalt shingle according to claim 1, characterized in that: The fiber membrane is prepared by using 3-methoxy-2-methylchloromethacrylonitrile through magnetic field-electrospinning.
4. The highly flame retardant and anti-corrosion fiberglass asphalt shingle according to claim 1, characterized in that: The flame retardant is prepared from 3-isocyanatopropyltriethoxysilane-modified pentaerythritol phosphate and butyl acrylate.
5. The highly flame retardant and anti-corrosion fiberglass asphalt shingle according to claim 1, characterized in that: The dual curing is respectively cured by moisture and UV light.
6. A method for preparing highly flame-retardant and anti-corrosion glass fiber asphalt shingles, characterized in that: The method comprises the following preparation steps: (1) After drying nylon 66 at 120°C for 4 hours, add polypropylene F401 (4 to 6 times the mass of nylon 66), glass fiber (2 to 3 times the mass of nylon 66), polyphosphate melamine (0.1 to 0.3 times the mass of nylon 66), and polypropylene grafted maleic anhydride (0.7 to 0.9 times the mass of nylon 66), stir at 350 to 500 rpm for 30 to 90 minutes, perform microwave-assisted melt pultrusion to obtain long fibers, dry at 65 to 75°C for 10 to 14 hours, add No. 90 matrix asphalt (270 to 350 times the mass of nylon 66), heat to 105 to 130°C, stir evenly, pour into a mold, and cure at 50 to 70°C for 22 to 26 hours to obtain glass fiber asphalt shingles; (2) 3-methoxy-2-methylchloromethacrylonitrile, N,N-dimethylacetamide, and silicon dioxide are mixed in a mass ratio of 4:20:0.5 to 8:23:1, stirred at 300 to 400 rpm for 3 to 6 hours, and ultrasonicated at 21 kHz for 2 hours to obtain a spinning solution, and subjected to magnetic field-electrostatic spinning on glass fiber asphalt shingles in an environment of temperature of 25° C. and humidity of 30%, dried at 65 to 75° C. for 10 to 14 hours, and then graphene is sprayed with laser-assisted low pressure; (3) Pentaerythritol phosphate and dioxane are mixed in a mass ratio of 20:45 to 30:60, stirred at 300 to 400 rpm for 90 to 150 min, heated to 70 to 90° C., 0.15 to 0.25 times the mass of pentaerythritol phosphate of 3-isocyanatopropyltriethoxysilane is added dropwise at 0.7 g / s, reacted for 30 to 60 min, 0.9 to 1.2 times the mass of pentaerythritol phosphate of melamine polyphosphate is added, acetic acid is added until the pH value of the solution is 3 to 5, the reaction is continued for 2 to 4 h, cooled to room temperature, filtered, the solid is taken, washed with anhydrous ethanol 3 to 5 times, and dried at 65 to 75° C. for 4 to 5 h to obtain intermediate A; (4) Mix the intermediate A, butyl acrylate, polyolefin wax, tributyl phosphate, silicone gel, deionized water, and 2-hydroxy-2-methyl-1-phenylacetone in a mass ratio of 25:35:2:1.5:5:15:0.2 to 35:45:3:2:8:24:0.5, and stir at 1450 to 1600 rpm for 30 to 60 minutes to obtain a flame retardant; (5) The flame retardant is coated on the glass fiber asphalt shingles sprayed with graphene to a thickness of 0.3 to 0.8 mm, and double curing is performed to obtain highly flame retardant and anti-corrosion glass fiber asphalt shingles.
7. The method for preparing a highly flame-retardant and anti-corrosion glass fiber asphalt shingle according to claim 6, characterized in that: The process parameters of the microwave-assisted melt pultrusion in step (1) are: microwave power 260 W, melting tank temperature 250° C., traction speed 20 m / min, and screw speed 100 r / min.
8. The method for preparing a highly flame-retardant and anti-corrosion glass fiber asphalt shingle according to claim 6, characterized in that: The process parameters of the magnetic field-electrospinning in step (2) are: magnetic field intensity 0.3T, magnet spacing 2.5cm, spinning flow rate 10mm / min, positive voltage 25kV, negative voltage 2kV, and receiving distance 15cm.
9. The method for preparing a highly flame-retardant and anti-corrosion glass fiber asphalt shingle according to claim 6, characterized in that: The process parameters of the laser-assisted low-pressure spraying in step (2) are: spray gun preheating temperature 200-600°C, nitrogen pressure 0.8MPa, spraying distance 15cm, scanning speed 30mm / s, powder feeding rate 25g / min, and laser irradiation power 600W.
10. The method for preparing a highly flame-retardant and anti-corrosion glass fiber asphalt shingle according to claim 6, characterized in that: The conditions of the double curing in step (5) are as follows: the first moisture curing is carried out at a temperature of 25 to 27° C., a humidity of 75 to 80%, and a time of 22 to 26 hours; the second UV curing is carried out at a light source of UV light, a main wavelength of 365 nm, a power of 1 kW, an irradiation distance of 15 cm, and a time of 20 minutes.
Citation Information
Patent Citations
Flame-retardant modified colored asphalt felt
CN102797320A
Flame retardant nylon 66 composite plastic and preparing method therefor
CN103627170A